Solid Acid Catalyst WO3-ZrO2 for the Catalytic Deoxygenation of Jatropha Oil for the Preparation of Aviation Paraffin - Jiayu Lin; Jin Li; Shiyun Zhou; Yang Cao; Shurong Wang; Jiang Jiao (BioResources, 2022)
WO3-ZrO2 solid acid catalysts were prepared by the impregnation method and characterized by X-ray diffraction (XRD), transmission electron microscope (TEM), Brunauer-Emmett-Teller (BET), and pyridine adsorbed IR spectroscopy (Py-IR). The catalysts were used for catalytic deoxygenation of Jatropha curcas oil. The optimal conditions for the deoxygenation of the generated oil were obtained by response surface methodology based on Box-Behnken four-factor experiments. Response surface methodology (RSM) was applied while determining the optimal conditions for the Jatropha oil deoxygenation percentage. The rate was calculated based on Box-Behnken four-factor experiments, with reaction temperature, catalyst amount, reaction time, and reaction pressure as independent variables and the deoxygenation of Jatropha curcas oil as response values. The optimal reaction conditions obtained were a temperature of 370 °C, pressure of 2 MPa, time of 7 h, and catalyst amount of 0.22 g. The deoxygenation percentage of the generated oil under the optimal conditions was 95.1%, which was close to the theoretical value, indicating that the model was reliable. The generated oil contained more jet fuel components, with 68.1% C8-C16, 12.0% isoalkanes, 14.2% cycloalkanes, and 8.9% aromatic compounds under the optimum conditions. This study provides an effective and simple method for preparation of bio-aviation fuel.